Synthesis and Characterization of Polylactic Acid - Riaz, Tauheeda; Ikram Aujla, Muhammad; Akram Kashmiri, Muhammad; Shahzadi, Tayyaba; Asghar, Amina; Ismail, Tariq (Asian Journal of Chemistry, 2011)
Polylactic acid is among the most important biodegradable polymers. To explore the feasibility of making polylactic acid through cheap and easy to use methods, the direct polycondensation of lactic acid at 200 ºC under vacuum was investigated. Five samples of lactic acid were heated under vacuum. In three samples stannous chloride, glycerin and polyacrylamide gel were used as catalyst. Two samples were without the catalyst and heated at pressure 100 mm Hg with different time duration. The effects of catalysts and reaction time on the molecular weight and yield were studied. The polymer was characterized by infrared spectroscopy. The viscosity of the polymer was determined by Brookfield viscometer. The results showed that polymer which was heated under vacuum at 200 ºC without the use of catalyst, had highest yield, highest viscosity and highest molecular weight.